Low Density Solvent-Based Dispersive Liquid-Liquid Microextraction for the Determination of Synthetic Antioxidants in Beverages by High-Performance Liquid Chromatography - Hasan Çabuk; Mustafa Köktürk (The Scientific World Journal)
A simple and efficient method was established for the determination of synthetic antioxidants in beverages by using dispersive liquid-liquid microextraction combined with high-performance liquid chromatography with ultraviolet detection. Butylated hydroxy toluene, butylated hydroxy anisole, and tert-butylhydroquinone were the antioxidants evaluated. Experimental parameters including extraction solvent, dispersive solvent, pH of sample solution, salt concentration, and extraction time were optimized. Under optimal conditions, the extraction recoveries ranged from 53 to 96%. Good linearity was observed by the square of correlation coefficients ranging from 0.9975 to 0.9997. The relative standard deviations ranged from 1.0 to 5.2% for all of the analytes. Limits of detection ranged from 0.85 to 2.73 ng mL−1. The method was successfully applied for determination of synthetic antioxidants in undiluted beverage samples with satisfactory recoveries.